2021
DOI: 10.3390/cancers13194857
|View full text |Cite
|
Sign up to set email alerts
|

gsp Mutation Is Not a Molecular Biomarker of Long-Term Response to First-Generation Somatostatin Receptor Ligands in Acromegaly

Abstract: Background: It is still controversial if activating mutations in the stimulatory G-protein α subunit (gsp mutation) are a biomarker of response to first generation somatostatin receptor ligands (fg-SRL) treatment in acromegaly. Thus, we aimed to evaluate whether gsp mutation predicts long-term response to fg-SRL treatment and to characterize the phenotype of patients harboring gsp mutations. Methods: GNAS1 sequencing was performed by Sanger. SST2 and SST5 were analyzed by immunohistochemistry (IHC) and real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…high AIP mutation status, low expression of E-cadherin and high expression of Ki-67 are considered good candidates to benefit from pasireotide treatment (12,18,(39)(40)(41)(42)(43)(44)(45). Despite the potential of these indicators, limited comprehensive studies and routine clinical practices make it challenging for clinicians to use these markers for patient selection, leading to a reliance on imaging and patient history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…high AIP mutation status, low expression of E-cadherin and high expression of Ki-67 are considered good candidates to benefit from pasireotide treatment (12,18,(39)(40)(41)(42)(43)(44)(45). Despite the potential of these indicators, limited comprehensive studies and routine clinical practices make it challenging for clinicians to use these markers for patient selection, leading to a reliance on imaging and patient history.…”
Section: Discussionmentioning
confidence: 99%
“…While high SSTR2 density is a good predictor of (12,18,43,44). Additionally, GH-secreting adenomas with mutations in the stimulatory G-protein alpha subunit, showing higher SSTR5 expression, may be more responsive to pasireotide (45).…”
Section: Methodsmentioning
confidence: 99%
“…At the pathological level, GHomas with high values of Ki67 and sparsely granulated (SG) pattern display a poorer response to SRLs [48], which is associated with a lower density of SST2 at the cell membrane of SG tumors, and a T2-hyperintensity signal on the MRI [49,50]. Recently, Wildemberg et al showed, in an elegant study, that somatic mutations of the gsp oncogene, identified in nearly 40% of GHomas, were not predictive of response to SRLs [51]. Familial predisposition to acromegaly has been known since the end of the 1990s [52], and germline mutations of the AIP (Arylhydrocarbon receptor interacting protein) gene are found in approximately 15% of FIPA (Familial Isolated Pituitary Adenoma) syndrome cases [53].…”
Section: Gh-secreting Pt (Acromegaly)mentioning
confidence: 99%
“…Acromegaly is caused, in the vast majority of cases, by a sporadic GH-secreting pituitary adenoma [ 4 ]. About 40% of these tumors have somatic mutations in the stimulatory G protein alpha-subunit 1 ( GNAS1 ) gene [ 17 , 18 ]. Germline mutations in the aryl hydrocarbon receptor-interacting protein ( AIP ) gene can be found in approximately 4 to 12% of patients with apparently sporadic acromegaly, especially if they are young (age < 30 years old) and carry macroadenomas [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%